Politiques publiques de développement à la frontière franco-brésilienne : une ignorance mutuelle - Madeleine Boudoux d’Hautefeuille (Confins)
Many peripheral border areas of national States around the world are affected by public territorial policies aiming to their development. The Franco-Brazilian border between French Guiana, a French overseas department and region, and Amapá, a Brazilian federal State, is the case study in which we examine here these policies, focusing not on their efficiency, but on their coincidence. This review reveals a major political gap between France and Brazil : based on national dynamics implemented since the mid-twentieth century, but also with some local specificities, they do not have the same geographic scope, or the same nature, or the same goals or even the same kinds of drivers. Based primarily on the analysis of documents related to those public policies, this paper successively discusses those implemented on the French side and then on the Brazilian side. This leads to a comparative tabular and mapping assessment highlighting clear differences and a relative mutual ignorance.